Premature tooth loss in maintenance hemodialysis patients - WANG Fang; ZHENG Xiao-yu; TU Juan; YANG Jun; RUAN Jie; XU You-ping; HAN Zhi-wu (Linchuang shenzangbing zazhi)
Objective To evaluate premature tooth loss in patients on hemodialysis.Methods The case group compromised 68 patients with end-stage renal disease(ESRD) on hemodialysis in Blood Purification Center of the 161 st Hospital of PLA from Jan.2015 to Jan.2016.A control group was consisted of 68 individuals matched for sex and age(± 3 years) with a glomerular filtration rate >90 mL/min.All participants underwent intraoral examination,gathering information on dental and periodontal status.Tooth loss,dental caries and periodontal disease status were recorded.Differences between two groups were compared.Results The number of missing teeth was significantly greater(P = 0.002) in case group(11.4 ± 8.2) than in control group(7.6 ± 5.8).The index of DMFT was significantly higher(P=0.003) in case group(15.5 ±8.1) than in control group(11.9 ± 5.9).There was no significant difference(P = 0.24) in the number of decayed teeth between the case group(2.1 ±1.4) and the control group(2.4± 1.5),and no significant difference(P = 0.24) in the mean number of filled teeth between the case group(1.7 ± 1.7) and the control group(1.9 ± 1.4).Periodontal disease status,including plaque index(1.78 ± 0.87 in the case group vs.1.24 ± 0.65 in the control group),gingival index(1.39 ± 0.87 in the case group vs.0.92 ± 0.57 in the control group),periodontal probing depth(5.37 ± 1.84 mm in the case group vs.3.08 ± 1.03 mm in the control group),clinical attachment loss(5.68 ± 1.92 mm in the case group vs.3.26 ± 0.92 mm in the control group)and tooth mobility(1.79 ± 0.57 in the case group vs.0.57 ± 0.50 in the control group),was significantly worse in hemodialysis patients than in control group(P = 0.000).Ten(14.7%) fully edentulous individuals were detected in the study group and 3(4.4%) in the controls.The percentage of fully edentulous patients were significantly higher in study group than in the controls(P = 0.041).Conclusions Premature tooth loss and poor periodontal status are common in hemodialysis patients.